Persepsi Mahasiswa Pendidikan Jasmani Unimuda Sorong terhadap Integrasi Teknologi Digital pada Mata Kuliah Praktik - Muh. Irwan Saputra; Risnawati; Farcham Mulloh (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to analyze Physical Education students’ perceptions of digital technology integration in practical courses at Universitas Pendidikan Muhammadiyah Sorong. This research employed a quantitative approach using a descriptive survey design. The participants consisted of 50 Physical Education students selected through purposive sampling. Data were collected using a perception questionnaire based on a five-point Likert scale, covering five main aspects: ease of use of digital technology, perceived usefulness, effectiveness in practical learning, learning motivation, and barriers to digital technology integration. The instrument was tested for validity and reliability, with the results indicating that all items were valid and reliable (Cronbach’s Alpha = 0.884). Data were analyzed using descriptive statistics, including mean scores and percentages. The findings revealed that students’ perceptions of ease of use were in the high category (mean = 4.12), perceived usefulness was very high (mean = 4.21), effectiveness of practical learning was high (mean = 4.09), and learning motivation was very high (mean = 4.21). Meanwhile, the barriers to digital technology integration were categorized as moderate to high (mean = 3.59), particularly related to limited facilities, internet connectivity issues, and the suitability of digital technology for certain practical courses. In conclusion, physical education students demonstrate positive perceptions toward digital technology integration in practical learning; however, institutional support and appropriate implementation strategies are required to ensure optimal and sustainable use of digital technology in physical education learning. Keywoards: Physical Education, Student Perception, Practical Learning, Digital Technology